2013
DOI: 10.1161/circimaging.113.000092
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Prognosis of Coronary Artery Calcium Scoring in Nontriggered Thoracic Computed Tomography

Abstract: Compared with electrocardiography-triggered CT, nontriggered CT is extensively used. In 2007, 13.6 million nontriggered thoracic CT examinations were performed in the United States, in contrast to 0.7 million electrocardiography-triggered CT examinations for calcium scoring. 7 Recent trial results have increased the interest in lung cancer screening by thoracic CT.8 Thus, the number of nontriggered examinations will likely further increase. Age and smoking, the current selection criteria for lung cancer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 31 publications
5
121
1
11
Order By: Relevance
“…There were 8.8% false negative NCCT for CAC noted on the gated scans, and 19.1% underestimation of high CAC scores. 63 Most recently, 4544 subjects underwent both 3mm gated CAC scans and 6 mm standard nongated chest CT scans by electron beam computed tomography, with a 6 year follow up for all cause mortality. 64 There were 157 deaths, matched 1:3 to 494 survivor controls.…”
Section: Nongated Ct Examinationsmentioning
confidence: 99%
“…There were 8.8% false negative NCCT for CAC noted on the gated scans, and 19.1% underestimation of high CAC scores. 63 Most recently, 4544 subjects underwent both 3mm gated CAC scans and 6 mm standard nongated chest CT scans by electron beam computed tomography, with a 6 year follow up for all cause mortality. 64 There were 157 deaths, matched 1:3 to 494 survivor controls.…”
Section: Nongated Ct Examinationsmentioning
confidence: 99%
“…It is estimated that 7 million Americans would be eligible for such a screening (10), a number that of course does not include the millions of additional adults who undergo a chest CT for other reasons. The strong association between smoking and CV risk, explains the high prevalence of CAC >0 that was over 50% in many of the studies (49), and the proportion of individuals with the highest category of CAC (similar to an Agatston score >400) that was approximately 20%.…”
Section: Resultsmentioning
confidence: 99%
“…In a systematic review and meta-analysis by Xie et al (49), found a strong agreement in CAC scores categorization between non-triggered CT and electrocardiographytriggered CT. Based on five studies (49-53) that authors concluded that compared with electrocardiographytriggered CT, a high calcium score category in nontriggered CT is a fairly reliable finding. However they found that nontriggered CT yielded false-negative score in 8.8% of individuals, and underestimated high score in 19.1%.…”
Section: Gated Vs Ungatedmentioning
confidence: 94%
“…In addition, previous cohort studies by Itani et al 23) and Ikeda et al 42) evaluated whether the presence of CAC is associated with cardiac mortality or cerebral atherosclerosis using conventional spiral CT. Although this method does not replace dedicated ECG-triggered CT scanning, calcium scoring in the setting of non-triggered CT has the potential to be used to evaluate evidence for diagnostic and prognostic purposes 41) .…”
Section: Cac Score and Coronary Ctamentioning
confidence: 99%